A comparative study of catalogers' perceptions on the use of Bibliofile as a cataloging tool - Cruz, Annelyn G. (1998)
This study focuses on the catalogers' perception on the use of BiblioFile as a cataloging tool. The study seeks to: 1) find out what features of BiblioFile are useful in the libraries under study; 2) know the perceptions of catalogers regarding BiblioFile; 3) know how satisfied the catalogers are with BiblioFile; 4) know the differences between BiblioFile and other cataloging tools; 5) point out the strengths and weakenesses of BiblioFile; and 6) give suggestions and recommendations which may be beneficial to the catalogers who are using it. The descriptive research method was used, with questionnaires and informal interviews.